Inter-cell interference coordination in LTE-A HetNets: a survey on self organizing approaches - Hasan, Mohammad Kamrul; Ismail, Ahmad Fadzil; Hassan Abdalla Hashim, Aisha; Abdullah, Khaizuran; Mohd. Ramli, Huda Adibah; Islam, Shayla; Abdelhaleem Saeed, Rashid (IEEE, 2013)
Heterogeneous Networks (HetNet) are multi-mode, multi-layer, and multi-band structured and utilize cells of varying sizes. The goal behind the implementation of HetNets involves incrementing the capacity of the established network, modifying spectrum use, lowering the capital and operating costs, and offering steady user-based experience of network architecture. However, these random small cell deployments cause severe problems and results interference in the network. Therefore, the ultimate is the total system performance degradation and this interference becomes a key challenge in HetNet. This article investigates the performances of the current trends and approaches of interference in self organizingnetwork for LTE-A. Key Words—